Physicochemical and Bacteriological Analysis of Groundwater Quality of Kathmandu Valley - Maharjan, Sujan; Joshi, Tista Prasai; Koju, Rashim; Shrestha, Sujan Man (Journal of Natural History Museum, 2020)
The limited availability, accessibility and deterioration of the water quality in Kathmandu valley have led to the high demand of ground water. This study aims to evaluate ground water quality of the Kathmandu valley. In this study, the physio-chemical parameters of water samples were performed using standard procedures. Also, total coliforms were enumerated using standard membrane filtration technique to quantify the bacterial contamination. Water samples were collected from July 2017 to July 2018. The results revealed that 56% and 73% of well and boring water samples, respectively exceeded standard value of iron recommended by National Drinking Water Quality Standards, 2005. Likewise, ammonia content was higher in 41% of well water and 35% of boring water samples than standard. However, few numbers of water samples were contaminated with arsenic (0.27% and 2.6% of well and boring water samples, respectively) and nitrate (3% and 8% of well and boring water samples, respectively). Besides, 96% of well water samples and 88% of boring water samples were contaminated with total coliform bacteria. Our data indicated that groundwater quality of Kathmandu valley was poor, which was not suitable for direct drinking purposes. Therefore, regular monitoring and treatment of groundwater is recommended before using accordingly.